PERBEDAAN METODE SAJIAN DINGIN KOPI TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK KOPI ARABIKA DARI BERBAGAI DAERAH DI INDONESIA - Hermanto Hermanto; Kiki Yuliati; Ervina Hasian Christifani; Dwi Wulan Sari (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
The aim of this study was to determine the effect of differences cold serve coffee methode and origin growth from different region in Indonesia on chemical and organoleptic characteristics. This study used factoriall Randomized Block Design (RBD) with two factors. The treatments in this study were (A) differences origin growth of arabica coffee from different region in indonesia with using one treatment factor and three repetitions with repetitions considered as block and (B) cold serve coffee method. Parameters in this study included chemical characteristic (ranking test) and chemical characteristics (antioxidant value, total phenolic compound, total acid level, and pH). The result showed that as the differences of origin growth coffee given different respond on brewing method significantly affected the costumers ranking preference (appearance, taste, acidity, aftertaste, balance and overall), antioxidant value, total phenolic compound, and pH level